A three-dimensional graphene/Fe3O4/carbon microtube of sandwich-type architecture with improved wave absorbing performance. (15th July 2016) - Huang, X.; Yan, X.; Xia, L.; Wang, P.; Wang, Q.; Zhang, X.; Zhong, B.; Zhao, H.; Wen, G.
Abstract: We employ a facile approach to fabricate the novel graphene/Fe3 O4 /carbon microtube-nanocomposite with the hierarchical sandwich-type architecture by the addition of the trace amount of the carbon microtubes. This new microstructure effectively avoids the agglomeration of graphene and keeps the characteristic of stronger and broader absorption with lighter density. Results indicate that the graphene/Fe3 O4 /carbon microtube-nanocomposite with the sandwich-type architecture has a strong RL (about − 50 dB) at a band of about 4 GHz, highlighting its importance for microwave absorbing applications. Graphical abstract: We concern a facile approach to fabricate the novel graphene/Fe3 O4 /carbon microtube nanocomposites with the hierarchical sandwich-type architecture by the addition the trace amount of the carbon microtubes. This new microstructure effectively avoids the agglomeration of graphene and keeps the characteristic of stronger and broader absorption with lighter density. Results indicate that the graphene/Fe3 O4 /carbon microtube nanocomposites with the sandwich-type architecture have a strong RL (about − 50 dB) with a band of about 4 GHz, highlighting its importance for microwave absorbing applications.